The Dynamics and Determinants of Bullying Victimisation - Georgios Marios Chrysanthou; Chrysovalantis Vasilakis (Institute of Labor Economics (IZA), 2018)
We study the determinants and longitudinal evolution of nine types of adolescent (verbal, physical, indirect) bullying at school and domestically using the Understanding Society dataset during 2009-13. Family support is the most prominent protective factor against bullying. Applying joint maximum likelihood estimation (MLE) for dynamic discrete responses, we investigate potential simultaneous determination of bullying and family support. The estimates indicate that bullying disclosure might be uncommon. The probability of escaping/suffering victimisation is inversely/positively related to previous bullying intensity, respectively. Family income increases domestic indirect aggression but, reduces direct aggression and non-domestic bullying as does living in a high income region.
Keywords: C25; C35; J12; J13; 330; bullying; dynamic discrete response; simultaneity; unobserved heterogeneity